أثر ابن رشد على الفكر الغربي - الصاوي، أحمد محمد إبراهيم Alsawi, Ahmed Mohammed Ibrahim (جامعة الأزهر - كلية الدراسات الإسلامية والعربية للبنات بكفر الشيخ, 2018)
يتكون البحث من أربعة مباحث يسبقها مقدمة ويتلوها خاتمة 1. المقدمة وتشتمل على أهمية الموضوع وسبب اختياره، وخطة البحث وخطواته 2. المبحث الأول: ابن رشد حياته ومؤلفاته تحدثت فيه عن اسمه ونسبه وكنيته، وعن مولده، وعن حياته، وعن علاقته بابن طفيل، وعن مؤلفاته، ووفاته رحمه الله تعالى. 3. المبحث الثاني: ترجمة فلسفة ابن رشد إلى العالم الغربي، ويسلط هذا المبحث الضوء على عملية ترجمة ونقل التراث الإسلامي إلى العالم الغربي، وخاصة تراث ابن رشد، والآثار التي تركتها هذه الترجمات وموقف الكنيسة منها، فيقدم خلاصة عن أهم الأسباب الاقتصادية والثقافية التي دفعت العالم الأوروبي لنقل وترجمة تراث المسلمين وبينت ذلك من خلال مطلبين: المطلب الأول: أسباب اللجوء إلى التراث العربي الإسلامي المطلب الثاني: أهم المدن التي احتضنت عملية الترجمة لتراث ابن رشد: 4. المبحث الثالث: أثر ابن رشد على مفكري الغرب في القرون الوسطى ويبين هذا المبحث أن العلماء والباحثون القدامى والمعاصرون مستشرقون ومسلمون يثبتون بما لا يدع مجلا للشك الأثر العظيم الذي أحدثه ابن رشد على الفكر الغربي في القرون الوسطى ووضحت ذلك من خلال المطالب الآتية: المطلب الأول: الدراسات الغربية المؤيدة لأثر "ابن رشد" على الفكر الأوروبي في العصور الوسطى مثل دراسات أرنست رينان، ودراسات "بيير موندوريه Pierre mondorret"، ودراسات "أسين بلاثيوس asinpalacios: المطلب الثاني: الدراسات الشرقية المؤيدة لأثر "ابن رشد" على الفكر الأوربي في العصور الوسطى مثل دراسات محمد يوسف موسى، وعباس محمود العقاد، ومحمود قاسم، وفرح أنطون المطلب الثالث: إثر ابن رشد على العقيدة الكنسية في الغرب في العصور الوسطى 3. المبحث الرابع: أثر ابن رشد على مفكري الغرب في العصر الحديث بينت فيه أن معظم الباحثين ركزوا على تأثير الفلسفة الإسلامية على الفكر الأوربي في القرون الوسطى، ولم يركزوا على التأثير الفلسفي الإسلامي على الفكر الغربي في العصر الحديث، ومن خلال هذا المبحث ألقيت الضوء على هذا الأمر وأشرت إلى بعض جوانب التأثير لا كلها من خلال أثر ابن رشد على الفكر الغربي في العصر الحديث مبينا رأي الرافضين لهذا التأثير من خلال مطلبين: المطلب الأول: المؤيدون لأثر ابن رشد على الفكر الغربي الحديث مثل عباس محمود العقاد، وذكي نجيب محمود، وأحمد أمين، وعبد المعطي بيومي ثم كانت الخاتمة: وتحدثت فيها عن نتائج البحث وتوصياته
The research consists of four questions preceded by an introduction and followed by a conclusion 1- Introduction includes the importance of the subject and the reason for its selection, and the research plan and steps 2- The first subject: Ibn Rushd his life and his writings talked about his name and descent and his nickname, and his birth, and his life, and his relationship with Ibn Tufail, and his writings, and his death, God's mercy The second section deals with the translation of Ibn Rushd's philosophy into the Western world. This course highlights the process of translating and transferring the Islamic heritage to the Western world, especially Ibn Rushd's heritage, and the implications of these translations and the position of the Church. The European World for the transfer and translation of the heritage of Muslims and demonstrated this through two demands: First: Reasons for resorting to the Arab-Islamic heritage The second demand: the most important cities that embraced the translation process of the heritage of Ibn Rushd: 4 The third topic: the impact of Ibn Rushd on the thinkers of the West in the Middle Ages This study shows that ancient and contemporary scholars and scholars are orientalists and Muslims who prove beyond any doubt the great impact that Ibn Rushd had on Western thought in the Middle Ages and explained this through the following demands: First demand: Western studies in support of Ibn Rushd's influence on medieval European thought such as Ernst Renan's studies, Pierre Mondorret studies, and Asinpalacios studies: The second demand: the Oriental studies in support of Ibn Rushd's influence on European thought in the Middle Ages, such as the studies of Muhammad Yusuf Musa, Abbas Mahmoud al-Akkad, Mahmoud Qassem, Farah Anton Third: Ibn Rushd's influence on the ecclesiastical creed in the West in the Middle Ages 3 -The fourth topic: Ibn Rushd's impact on the thinkers of the West in the modern era showed that most researchers focused on the influence of Islamic philosophy on European thought in the Middle Ages, and did not focus on the Islamic philosophical influence on Western thought in modern times, and through this section shed light On this matter and I pointed to some aspects of the impact, not all of them through the impact of Ibn Rushd on Western thought in modern times, indicating the rejection of this effect by two demands: First: Supporters of the impact of Ibn Rushd on modern Western thought such as Abbas Mahmoud Akkad, and intelligent Naguib Mahmoud, Ahmed Amin, Abdulmuti Bayoumi Then the conclusion was: I spoke about the research findings and recommendations
Keywords: الفلسفة الإسلامية -- الفكر الغربي -- الفلاسفة المسلمين -- ابن رشد